2020
DOI: 10.1177/1054773820933449
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Clusters’ Content, Stability and Correlation with the Quality of Life in a Heterogeneous Group of Cancer Patients: A Large-Scale Longitudinal Study

Abstract: Cancer-related symptoms can negatively affect the quality of life, hinder or delay treatment, and increase suffering. This study aimed to explore symptom clusters among Jordanian cancer patients. A longitudinal survey design was used. The sample consisted of 1280 cancer patients treated in three selected hospitals. Two-thirds of the participants were female (63.5%) with a mean age of 52.7 SD 13.8 years and 40.3% had breast cancer. Five clusters were identified, the first was the psychological cluster of eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In addition, a recent literature review on symptom clusters reported the most common ones as the psychological, gastrointestinal, and nutritional clusters (Harris et al, 2021), which partly resembles our own findings; we also identified four clusters, and the exact content within each cluster is different (Harris et al, 2021). Other studies reported that certain clusters remain stable over time (Al Qadire et al, 2020; Molassiotis et al, 2010; Skerman et al, 2012). The time aspect and stability of the identified symptom clusters were not considered in our study and therefore need to be investigated further, combined with the occurrence and distress dimensions in a similar heterogeneous cancer sample.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, a recent literature review on symptom clusters reported the most common ones as the psychological, gastrointestinal, and nutritional clusters (Harris et al, 2021), which partly resembles our own findings; we also identified four clusters, and the exact content within each cluster is different (Harris et al, 2021). Other studies reported that certain clusters remain stable over time (Al Qadire et al, 2020; Molassiotis et al, 2010; Skerman et al, 2012). The time aspect and stability of the identified symptom clusters were not considered in our study and therefore need to be investigated further, combined with the occurrence and distress dimensions in a similar heterogeneous cancer sample.…”
Section: Discussionmentioning
confidence: 97%
“…Based on our current findings, there are common symptom clusters among patients with cancer receiving chemotherapy. The stability of symptom clusters across dimensions has been tested and confirmed in patients with different types of cancer such as lung cancer (Russell et al, 2019), breast cancer (Sullivan, Leutwyler, Dunn, Cooper, et al, 2018), and in a heterogeneous group of cancer patients (Al Qadire et al, 2020) receiving chemotherapy. In the current study, the symptom clusters identified were also relatively stable across the dimensions of occurrence and distress, regardless of cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…PRO that includes health status is also viewed as a crucial indicator of treatment effectiveness in clinical trials and is an essential criterion for drug approval, as required by the U.S Food and Drug Administration (FDA) from 2006 [12]. However, both physical and psychosocial symptoms can adversely affect QoL and daily functions [13]. Research shows that improvement in the QoL of patients is of great significance for their anticancer treatments, long-term rehabilitation, and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the everyday life challenges experienced by people undergoing cancer therapy, all cancer therapies can cause burdensome side effects, and patients experience several symptoms, which often occur in clusters and negatively affect their QoL. 8 , 9 QoL often varies depending on health status and symptom experience; some researchers thus define aspects of QoL that are related to health as “health-related QoL.” 17 Compared to the frequently studied chemotherapy-induced side effects, 1 fewer studies have looked at the patient-reported side effects commonly experienced during radiotherapy. 4 , 6 Healthcare practitioners often underestimate symptom occurrence and symptom burden during radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…People undergoing cancer therapy face many challenges in everyday life that decrease their Quality of Life (QoL), for example, the burden of cancer-therapy-induced side effects. [1][2][3][4][5][6][7][8][9][10][11] Each individual has his/her own way of dealing with these challenges, often by using non-pharmacological or self-care management strategies. 7 Effective pharmacology medical therapies to reduce some of the side effects exist but are often costly 12 and may produce drug interactions and additional side effects.…”
Section: Introductionmentioning
confidence: 99%